POLITIK PEREMPUAN BERBASIS GENDER - Luluk Dwi Kumalasari (Prodi Sosiologi FISIP Universitas Teuku Umar, 2016)
The increasing number of women, who concern in politics and have sensitivity and awareness about the important of social relation, economics, law, culture issues among women and men will trigger gender equality in politics. However, it is not easy as imagined due to patriarchy concept on Indonesian women which have less access to gain high achievement in public sectors. On the other hand, the idealization of political participation of Indonesian women in political practices still not comparable to the number of Indonesian women. Therefore, women movement especially on politics, quality improvement through education, and support women to get excellent prestation in front stage (public area), it is a effective way to give opportunity, appreciation and gender equality for women. Keywords: Politics Representation, gender, sensitivity and awareness